Transformative Leadership and Work Commitment in Improving the Quality of Madrasah Education - Muchammad Eka Mahmud; Chusnul Muali; Muhammad Ali Sulton (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study describes transformative leadership and work commitment in improving the quality of education at an Aliyah level educational institution in Probolinggo Regency. This research uses a qualitative case study approach. The type of research used is a single instrumental case study, namely efforts to improve the quality of education through principal leadership and teacher loyalty. The data analysis used is theme analysis. The purpose of this study is to provide additional insight into efforts to improve the quality of education through transformative leadership and work commitment. The results of this study are that there are several things in the application of transformative leadership and work commitment in improving the quality of education at an Aliyah level educational institution in Probolinggo Regency, namely (1) Teamwork, (2) Motivation, (3) A pleasant work climate.